Analisis Sengketa Pengangkatan Kepala Desa Berdasarkan Putusan Pengadilan Tata Usaha Negara Medan Nomor 43/G/2023 Menurut Perspektif Fiqh Siyasah dan Undang Undang Desa Nomor 6 Tahun 2014 - M. Syarif Perdana; Syofiaty Lubis (CV Rewang Rencang, 2024)
Disputes related to the appointment of village heads are an issue that often arises in the context of village government in Indonesia. This study aims to examine the conflict of closing village heads based on the Decision of the State Administrative Court (PTUN) of Medan Number 43/G/2023, with the approach of Fiqh Siyasah and Village Law Number 6 of 2014. The research uses a case study method with a qualitative and descriptive-analytical (normative-juridical) approach. This article also reviews the legal and social impact of the PTUN decision, as well as provides recommendations for future improvements in village governance. The findings of the study show that the Medan State Administrative Court canceled the decision of the South Tapanuli Regent because it was considered to violate the principles of good governance. In the perspective of Fiqh Siyasah (Qadha'iyyah), this decision is in accordance with the values of justice (al-'adl), legal certainty (al-yaqin), and benefit (maslahah) in the administration of the islamic government.